Physico-chemical properties of extrusion-texturized soybean - Del Rosario, O. M. (Philippine Agricultural Scientist, The (Formerly the Philippine Agriculturist), 2001)
The effects of raw material moisture, oil content, and temperature on the texturization of soyflour by extrusion using a locally fabricated single-screw extruder were studied. Multiple regression analysis was used to evaluate the data and a response surface map was developed for each property. The fibrous appearance of extrudates was more prominent at temperature levels of 100-110 C, a moisture content of 30-40%, and an oil content of 10.5%. Textural integrity index (TII) increased with an increase in temperature and decreased with an increase in moisture content. The highest TII (0.75) was obtained from the extrudate of partially defatted soyflour (10.5% oil) at 40% feed moisture content and an extrusion temperature of 110 C. The nitrogen solubility index (NSI) of soyflour was reduced by as much as 88.8% after extrusion. The NSI of texturized materials ranged from 10.7% to 38.6%. NSI was directly related to moisture content but inversely to temperature. Water absorption capacity (WAC) increased after extrusion and ranged from 282% to 451.30% in the texturized materials. WAC increased with temperature up to 100 C and decreased with further temperature increases up to 110 C. WAC decreased at 16.5% oil content and then increased at 22.5%.